2011
DOI: 10.1089/vbz.2009.0251
|View full text |Cite
|
Sign up to set email alerts
|

A Serological and Molecular Study ofLeishmania infantumInfection in Cats from the Island of Ibiza (Spain)

Abstract: The aim of this study was to evaluate the prevalence of Leishmania infantum infection within a feline population by serologic and molecular methods and to identify associated risk factors. One hundred five cats living outdoors were studied. Sera were tested for IgG antibodies against L. infantum, Toxoplasma gondii, and feline immunodeficiency virus (FIV) and for the detection of feline leukemia virus (FeLV) p27 antigen by enzyme-linked immunosorbent assay (ELISA). L. infantum real-time polymerase chain reactio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

14
66
3
12

Year Published

2011
2011
2023
2023

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 73 publications
(95 citation statements)
references
References 43 publications
14
66
3
12
Order By: Relevance
“…in cats (SHERRY et al, 2011;SOBRINHO et al, 2012), a positive statistical association between infections by T. gondii and L. infantum and N. caninum and L. infantum, which was indicative of coinfections, was detected in this study. Numerous studies have reported immunosuppression caused by Leishmania spp., which could enhance the susceptibility to the parasite when immunosuppressive events are not involved.…”
Section: Discussionsupporting
confidence: 63%
“…in cats (SHERRY et al, 2011;SOBRINHO et al, 2012), a positive statistical association between infections by T. gondii and L. infantum and N. caninum and L. infantum, which was indicative of coinfections, was detected in this study. Numerous studies have reported immunosuppression caused by Leishmania spp., which could enhance the susceptibility to the parasite when immunosuppressive events are not involved.…”
Section: Discussionsupporting
confidence: 63%
“…In other studies, prevalence of Leishmania spp infection in cats by PCR-based tests was reported as 8.7% (Sherry et al, 2011) and 25.7% (Martín-Sánchez et al, 2007) in Spain, 10% in Iran (Hatam et al, 2010), and 20.3% in Portugal (Maia et al, 2010). Peripheral blood has been the most commonly used specimen in PCR-based feline surveys and positive results ranged from 0.3% to 60.7%, among cats living in regions endemic for canine and/or human leishmaniosis (Martín-Sánchez et al, 2007;Tabar et al, 2008;Maia et al, 2008;Ayllon et al, 2008;Maia et al, 2010;Sherry et al, 2011;Millán et al, 2011;Ayllón et al, 2012;Vilhena et al, 2013).…”
Section: Discussionmentioning
confidence: 85%
“…Peripheral blood has been the most commonly used specimen in PCR-based feline surveys and positive results ranged from 0.3% to 60.7%, among cats living in regions endemic for canine and/or human leishmaniosis (Martín-Sánchez et al, 2007;Tabar et al, 2008;Maia et al, 2008;Ayllon et al, 2008;Maia et al, 2010;Sherry et al, 2011;Millán et al, 2011;Ayllón et al, 2012;Vilhena et al, 2013). More recently in Greece PCR positivity in different tissues from cats ranged from 3.1% (conjunctival swab) to 16% (bone marrow), 18.2% (skin biopsy) and 13% (blood) in clinically normal cats and in cats with various clinical signs living in the region of Thessaly (central Greece) and Thessaloniki (north Greece), thus indicating the need for multiple tissue PCR testing in order to avoid underestimating of the true prevalence of the infection (Chatzis et al, 2014).…”
Section: Discussionmentioning
confidence: 99%
“…Several novel Trypanosoma spp. have been identified in a range of Australian native wildlife species (Smith et al 2008;Austen et al 2009;Averis et al 2009;Paparini et al 2011). Indeed, Trypanosoma spp.…”
Section: Discussionmentioning
confidence: 99%
“…Indeed, Trypanosoma spp. have been implicated in the demise of marsupial populations in swWA (Smith et al 2008;Averis et al 2009). …”
Section: Discussionmentioning
confidence: 99%